1995
DOI: 10.1115/1.2804539
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Analysis of Simple-Shear Sheet Specimens

Abstract: The shear properties of different simple-shear sheet specimens were investigated using the elastic-plastic finite element method. Tension loaded specimens with a shear zone formed at the center area between two transverse slots were adopted to analyze the shear properties of sheet metals under uniaxial tension. Specimens prepared by single material as well as by bonding two different strength materials together were both studied. Since the shear zone could not be kept free from bending stress during loading, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In order to meet the needs of designing high-performance aeroengines, many researchers have paid attention to the work of developing and studying single crystal nickel-based superalloys [4,5], and a series of excellent-performance single crystal superalloys have been prepared for several years. Some literatures have reported that the temperature-bearing and creep-resistance properties of single crystal nickelbased superalloys can be remarkably improved as the increasing content of the refractory elements, such as W and Re [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In order to meet the needs of designing high-performance aeroengines, many researchers have paid attention to the work of developing and studying single crystal nickel-based superalloys [4,5], and a series of excellent-performance single crystal superalloys have been prepared for several years. Some literatures have reported that the temperature-bearing and creep-resistance properties of single crystal nickelbased superalloys can be remarkably improved as the increasing content of the refractory elements, such as W and Re [6][7][8].…”
Section: Introductionmentioning
confidence: 99%